Effect of play therapy and storytelling on the anxiety level of hospitalized children: a randomized controlled trial - Fatemeh Abdi; Ali Karamoozian; Mostafa Lotfilou; Fatemeh Gholami; Negin Shaterian; Alireza Abasi Niasar; Ehsan Aghapour; Mohammadamin Jandaghian-Bidgoli (BMC Complementary Medicine and Therapies)
Abstract Background Children are anxious when hospitalized due to being away from home and undergoing treatment.This anxiety has an effect on their disease process, treatment, growth and development.Children’s anxiety has an effect on parents’ anxiety and can lead to lower level of cooperation among the children and their parents with the treatment team.the present study aimed to compare the effect of play therapy and storytelling on the anxiety of hospitalized children. Methods A randomized controlled trial study with a three-group design (play therapy, storytelling and control) was conducted in 75 children aged 3 to 10 years admitted to Imam Ali Alborz Hospital of Karaj, Iran between 2022–2023.The data before and after the intervention were collected by the Spence children’s anxiety scale and the face tool for anxiety assessment and analyzed by the Mixed effect model statistical method. Results There is a statistically significant difference between the anxiety score of the children for whom storytelling was used and control group. Also, among the two therapies of storytelling and play therapy, only storytelling therapy has a significant effect on reducing children’s anxiety.Regarding the time of measuring the anxiety score(the first, second, third day after the intervention), it was found that as this time increases, the children’s anxiety decreases significantly.morever, the children’s gender, age, and history of hospitalization are influencing factors. Conclusion Play therapy and storytelling play an effective role in controlling the anxiety of hospitalized children, although storytelling had a greater role in reducing the anxiety of hospitalized children than play therapy. It is suggested to provide the necessary conditions and facilities for the implementation of these methods in children’s inpatient departments. Trial registration https://irct.behdasht.gov.ir/ ,IRCT20220704055367N1,13/7 /2022.